A Protocol For Assessment of Body Mass Index, Serum Albumin And Serum Prealbumin Change In Elderly Edentulous Patients After Complete Denture Rehabilitation. - Purohit, Hetal; Pisulkar, Shweta Kale (International Journal of Psychosocial Rehabilitation, 2020)
The Aim of study is to determine the effect on Body Mass Index (BMI), Serum Albumin and Serum Prealbumin change after Complete Denture Rehabilitation in Elderly Edentulous Patients. Material and methodology: A Prospective Interventional of study is planned to determine the effect on patients BMI, Serum Albumin and Serum Prealbumin levels after Complete Denture rehabilitation. A sum total of 40 edentulous patients will be selected from the Out Patient Department (OPD) of the Department of Prosthodontics, Sharad Pawar Dental College, Sawangi, Wardha. All the patients will be provided written consent before their participation in the study (ANNEXURE I) the study was approved by institutional ethical committee- DMIMS (DU)/IEC/2018-19/7515. Statistical analysis: The data thus obtained will be tabulated for further statistical analysis. Data will be analyzed using descriptive and analytical statistical methods. Statistical significance of the mean differences between the measurements in the interval of 6 months will be tested using student paired t-test.